Estudio de prefactibilidad para la instalación de una planta productora de fideos a base de harina de cañihua - Acosta Pino, Sebastian Alberto (2021)
This work covers the pre-feasibility study for the implementation of a noodle production plant based on cañihua flour. First, the objectives of the company and the technical, economic and social justifications are presented. From these, the hypothesis of the work was raised. Likewise, the most important sources on which this study was based are presented. In the second chapter, we proceeded to define the main variables of the product to be marketed, together with an analysis of the industrial sector. In addition, it was defined that the project demand would be 155,433 kg of noodles. Subsequently, the optimal location of the plant was determined; which turned out to be the province of Melgar, in the City of Puno. Regarding the size of the plant, it was concluded that the market size is the limiting factor for the project. For the production process, the necessary technology was defined, as well as the sequence of key activities to be able to supply the company's demand. In the same way, the optimal layout of the plant was made based on a plot of 500 m2. Finally, the economic, financial and social evaluation of the project was carried out, which determined that the project is profitable and that it contributes significantly to the creation of jobs with a high added value.